ANEKA RAGAM SPIRITUALITAS DALAM KEBUDAYAAN KONTEMPORER - Naim, Ngainun (UIN Maliki Malang, 2010)
Spiritualism is an inseparable part of human existence. The reduction of this dimension will effect negatively for human existence. This causes the emergence of new phenomenon, or even culture, in the life of modern society. The phenomenon is the increase of their interest in spiritualism. Even though, spiritualism in this context is not always identical with religion. Even, this phenomenon cannot be separated from capitalism. Therefore, the spiritualism that develops recently has various forms, that is, (1) Spiritualism Secularization, (2) Spiritualism Immanence, (3) Spiritualism Libidinalisation, (4) Schizo-spiritualism, (5) Hybridspiritualism, and (6) Techno-spiritualism. Furthermore, there is also another expression of spiritualism, that is, the emergence of new religion or quasi-religion movement. The emergence of this movement is influenced by the effort to release from religious countercultures. Other manifestation of this spiritualism is in the form of fundamentalism movement. In extreme point, this movement can be seen from the emergence of extreme cult, such as those that teach tragic way of death.